Monte Carlo studies of stress fields and intermixing in ge/si(100) quantum dots - Sonnet, Philippe; Kelires, Pantelis C. (My University, 2002)
Intermixing in islands grown on semiconductor surfaces is an important effect, because it drastically alters the optoelectronic properties. Here, we demonstrate a direct simulational approach, based on the Monte Carlo method, which is able to extract with quantitative accuracy the composition profiles in quantum dots, and link them to the stress field. We apply this approach to Ge/Si pyramidal islands. We find that the profiles are not homogeneous, but show strong variations in both the lateral and vertical directions. Outstanding features, such as Si-rich rings in the island layers, are directly linked to the stress pattern. A limiting behavior of composition as a function of temperature and island size is predicted.
Keywords: Germanium; Silicon; Chemical analysis; Electronics; Monte Carlo method; Quantum theory